Measuring PM2.5, Ultrafine Particles, Nicotine Air and Wipe Samples Following the Use of Electronic Cigarettes. Issue 9 (9th March 2017) - Melstrom, Paul; Koszowski, Bartosz; Thanner, Meridith Hill; Hoh, Eunha; King, Brian; Bunnell, Rebecca; McAfee, Tim
Abstract: Background: Few studies have examined the extent of inhalation or dermal contact among bystanders following short-term, secondhand e-cigarette exposure. Objective: Measure PM2.5 (particles < 2.5 microns), UF (ultrafine particles < 100 nm), and nicotine in air and deposited on surfaces and clothing pre-/during/post- a short-term (2-hour) e-cigarette exposure. Methods: E-cigarettes were used ad libitum by three experienced users for 2 hours during two separate sessions (disposable e-cigarettes, then tank-style e-cigarettes, or "tanks") in a 1858 ft 3 room. We recorded: uncorrected PM2.5 (using SidePak); UF (using P-Trak); air nicotine concentrations (using air samplers; SKC XAD-4 canisters); ambient air exchange rate (using an air capture hood). Wipe samples were taken by wiping 100 cm 2 room surfaces pre- and post- both sessions, and clean cloth wipes were worn during the exposure and collected at the end. Results: Uncorrected PM2.5 and UF were higher ( p < .0001) during sessions than before or after. Median PM2.5 during exposure was higher using tanks (0.515 mg/m 3 ) than disposables (0.035 mg/m 3 ) ( p < .0001). Median UF during exposure was higher using disposables (31 200 particles/cm 3 ) than tanks (25 200 particles/cm 3 )( p < .0001). Median air nicotine levels were higher ( p < .05) during both sessions (disposables = 0.697 ng/L, tanks = 1.833 ng/L) than before (disposables = 0.004 ng/L, tanks = 0.010 ng/L) or after (disposables = 0.115 ng/L, tanks = 0.147 ng/L). Median accumulation rates of nicotine on surface samples were 2.1 ng/100 cm 2 /h using disposables and 4.0 ng/100 cm 2 /h using tanks; for cloth samples, it was 44.4 ng/100 cm 2 /h using disposables and 69.6 ng/100 cm 2 /h using tanks ( p < .01). Mean room ventilation rate was 5 air changes per hour during both sessions. Conclusions: Short-term e-cigarette use can produce: elevated PM2.5 ; elevated UF; nicotine in the air; and accumulation of nicotine on surfaces and clothing. Implications: Short-term indoor e-cigarette use produced accumulation of nicotine on surfaces and clothing, which could lead to dermal exposure to nicotine. Short-term e-cigarette use produced elevated PM2.5 and ultrafine particles, which could lead to secondhand inhalation of these particles and any chemicals associated with them by bystanders. We measured significant differences in PM2.5 and ultrafine particles between disposable e-cigarettes and tank-style e-cigarettes, suggesting a difference in the exposure profiles of e-cigarette products.